2022
DOI: 10.3390/en15196978
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Gas Jet Pump: A Review

Abstract: To promote the development and application of the liquid–gas jet pump (LGJP), the research status of its design theory, internal flow mechanism, structural optimization and practical application are reviewed. The development history of the LGJP is briefly reviewed, the latest research and application progress of the LGJP is introduced, and the pulse-type of LGJP, especially the centrifugal jet vacuum pump (CJVP), is emphatically discussed. The research and development direction of the LGJP is analyzed and prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…It was concluded that by integrating a Knock-out Drum to the system, the jet pump operates in a closed circuit and its efficiency is higher than operating in an open system. Zhang et al [15] recently reviewed the research and application status of liquid gas jet pumps, and highlighted the superiority and irreplaceability of these devices in many technological processes.…”
Section: Suction Chambermentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that by integrating a Knock-out Drum to the system, the jet pump operates in a closed circuit and its efficiency is higher than operating in an open system. Zhang et al [15] recently reviewed the research and application status of liquid gas jet pumps, and highlighted the superiority and irreplaceability of these devices in many technological processes.…”
Section: Suction Chambermentioning
confidence: 99%
“…Conservation of mass, energy and momentum for the water jet in the mixing throat can be expressed by Eqs (15), ( 16) and (17), respectively:…”
Section: ) Mixing Throatmentioning
confidence: 99%
“…A jet pump has the characteristics of a simple structure and safe and reliable operation, and it is widely used in the field of water conservancy effuser system and other fields (Xu et al, 2021;Zhang et al, 2022;Winoto et al, 2000). In order to better adapt to the diversity and complexity of the sprinkler irrigation system environment, related scholars have performed many experiments with jet pumps as research objects, with a view to revealing the hydraulic performance and internal flow structure of jet pumps and to provide data support for the application of the pumps in engineering practice (Lu et al, 2015a;Lyu et al, 2016;Aissa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of its primary objectives is to maximize the air intake while minimizing the swirl number. By incorporating the existing liquid-gas ejector water intake and suction technology, the objective is to address issues such as excessive fluid swirling and inadequate air intake at the outlet of the cleaning spray bar [19][20][21]. The CFD technique was used to simulate and analyze the swirl number of outlet mixed fluid, the inlet volume, and the specific flow conditions in the flow channel for each model.…”
Section: Introductionmentioning
confidence: 99%